Equality for same-sex couples the legal recognition of gay partnerships in Europe and the United States - Merin, Yuval (Chicago, [Ill.] : University of Chicago Press, 2002)
During the past three decades, nations all over the world have been debating whether to allow same-sex couples to marry, or at least grant these couples various rights associated with marriage. In 'Equality for Same-Sex Couples', Yuval Merin presents the first comparative study of the legal regulation of same-sex partnerships worldwide, as well as a unique survey of the status of same-sex couples in Europe.
Specialized.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Same-sex marriage -- Law and legislation -- Europe; Gay couples -- Legal status, laws, etc. -- Europe; Same-sex marriage -- Law and legislation -- United States; Gay couples -- Legal status, laws, etc. -- United States; Law; LGBTQ+ Interest; Society & culture: general; Gay & Lesbian studies; Jurisprudence & general issues; Constitutional & administrative law: general